Computer Simulation of Space Configuration of Low Frequency Magnetic Field in Magnetotherapy - Dimitrov, D. T. (Elektronika ir Elektrotechnika, 2005)
The goal of this article is to present the prototype of the simulation program for investigation of space configuration of lowfrequency magnetic 3d field used in magnetotherapy. The presented program is a 3D CAD program intended for non-professionals in electromagnetism. Therefore, the program can be used easy by physicians, also. The emphasis is on creating and interacting with a computer-based model of a system (configuration of coils). This model is being designed to test the magnetic properties of the coils and its influence on the human body in the process of magnetotherapy. The 3D simulation of the magnetic field, generated by the coil’s system is used as a tool for analyzing the behaviour of the magnetic field and as a feedback for the further interactive design of apparatuses for magnetotherapy. Ill. 4, bibl. 14 (in English; summaries in Lithuanian, English, Russian).